Predictive factors for compulsive exercise in adolescent athletes: a cross-sectional study - Fortier, M.; Rodrigue, C.; Clermont, C.; Gagné, A.; Brassard, A.; Lalande, D.; Dion, J. (Journal of Clinical Sport Psychology, 2025)
Although exercise is generally considered a healthy lifestyle habit, it may be problematic for some people. This has led to growing research on compulsive exercise—an uncontrollable urge for physical activity despite its deleterious effects. A maintenance model of compulsive exercise has been developed for adults exhibiting weight and shape concerns, weight control behaviors, and specific psychological states (including depression and anxiety) as predictive factors. We identified predicting factors for compulsive exercise in adolescent athletes using the same model framework. These athletes completed the compulsive exercise test and several well-validated psychometric measures. Gender-specific multiple regression models identified stronger drive for thinness, perfectionism, and body image investment in sport as significant predictors of compulsive exercise in boys and girls. Among girls, asceticism and bulimia symptoms were also significantly associated with compulsive exercise. These findings support the relevance of the model for clinical intervention and research on compulsive exercise in adolescent athletes.